2014
DOI: 10.1210/en.2013-1874
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Stress and Stress Coping Style Interact to Predict Metabolic Risk in Male Rats

Abstract: Both prenatal stress (PNS) exposure and a passive stress-coping style have been identified as risk factors for insulin resistance in rats. In the current study, we test the hypothesis that PNS and stress-coping style may interact in predicting susceptibility for metabolic disease. To test this hypothesis, adult male control and PNS offspring were behaviorally characterized using a defensive burying test to have either a passive or proactive stress-coping style. In adulthood, all rats were fed either a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In our recent studies, we found that PNS may modulate the stress-coping phenotype of the offspring. We showed that the distribution of the stress-coping behavior, expressed as the percentage time spent burying during the defensive burying test, was altered within the PNS rat population ( Boersma et al., 2014a ). In contrast to the control population, where about 16% of the rats were characterized as intermediate, there were no rats showing an intermediate stress-coping phenotype within the PNS offspring population ( Fig.…”
Section: Individual Differences – Susceptibility and Resiliencementioning
confidence: 99%
“…In our recent studies, we found that PNS may modulate the stress-coping phenotype of the offspring. We showed that the distribution of the stress-coping behavior, expressed as the percentage time spent burying during the defensive burying test, was altered within the PNS rat population ( Boersma et al., 2014a ). In contrast to the control population, where about 16% of the rats were characterized as intermediate, there were no rats showing an intermediate stress-coping phenotype within the PNS offspring population ( Fig.…”
Section: Individual Differences – Susceptibility and Resiliencementioning
confidence: 99%
“…Conversely, MS180 is a model of chronic postnatal stress that involves separating the pups from their mother for periods of 3 hr each day during the first 2 weeks of life (van Bodegom et al, 2017;Lehmann & Feldon, 2000;Meaney et al, 1996;Tractenberg et al, 2016). As adults, PNS and MS180 rats present a large repertoire of pathologies that include increased emotionality (Lajud, Roque, Cajero, Gutiérrez-Ospina, & Torner, 2012;Marrocco et al, 2014;Veenema, Blume, Niederle, Buwalda, & Neumann, 2006; Marta Weinstock, 2017) and metabolic risk (Boersma, Moghadam, Cordner, & Tamashiro, 2014;Ruiz et al, 2018;Vargas, Junco, Gomez, & Lajud, 2016). Recent evidence from our laboratory indicated that while MS180 increases baseline GC levels, it has no effect on the HPA axis response to a physical stressor; however, MS180 affects GC response to fasting (Ruiz et al, 2018).…”
mentioning
confidence: 99%
“…The shock probe burying test was used to characterize defensive behavior and coping style (Boersma et al, 2014). Rats were placed in a novel shoebox cage with clean bedding for 10 min of habituation.…”
Section: Shock Probe Defensive Buryingmentioning
confidence: 99%